From Example Problems
Jump to: navigation, search

Find the general solution of (D^{2}-1)y=2x+e^{{2x}}\,.

The auxiliary equation is m^{2}-1=0\, with roots m=-1,1\,.

The complimentary solution is y_{c}=Ae^{x}+Be^{{-x}}\,.

Guess the particular solution based on the inhomogenous term of the DE: y_{p}=c_{1}x+c_{2}e^{{2x}}\,.


Equate coefficients.


So c_{2}=1/3,\,\,\,c_{1}=-2\,.

y_{p}(x)=-2x+{\frac  {1}{3}}e^{{2x}}\,

The general solution is y=y_{c}+y_{p}\,.

y(x)=Ae^{x}+Be^{{-x}}-2x+{\frac  {1}{3}}e^{{2x}}\,

Main Page : Ordinary Differential Equations : Differential Operators